Single variable essential calculus early transcendentals - Stewart, James (Brooks/Cole Cengage Learning, 2013)
This book is for instructors who think that most calculus textbooks are too long. SINGLE VARIABLE ESSENTIAL CALCULUS, Second Edition, offers a concise approach to teaching calculus that focuses on major concepts, and supports those concepts with precise definitions, patient explanations, and carefully graded problems.